Pengaruh Konsentrasi Pupuk Organik Cair (POC) Tandan Kelapa terhadap Pertumbuhan Bibit Sawit (Elais guineensis) di Pre-Nursery - Riono, Yoyon (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
One of the most important plantation crops for Indonesia is oil palm (Elaeis guineensis Jacq), which functions as a staple export item and source of income for Indonesian plantations. In pre-nursery, you need to pay attention to the fertilizer applied, one of which is in liquid form. because liquid fertilizer is more easily absorbed by plants so that plant growth is more optimal. Liquid fertilizer can come from organic materials such as livestock manure, tofu waste, liquid plant waste. The main cause of decreased plant productivity is decreased soil fertility due to excessive and continuous application of inorganic fertilizers. Therefore, we need a way to maintain and improve soil fertility, one way that can be done is by providing organic fertilizer to the soil such as POC from coconut bunches. This research was conducted to determine the POC concentration of coconut bunches on the growth of oil palm in pre-nursery on peat media. The method used in this research is a non-factorial Randomized Block Design (RAK), the results of the analysis will be followed by the Tukey test (HSD) with a level of 5%. The research results showed that there was a real influence on all parameters such as plant height, stem base diameter, number of leaves, wet root weight, plant crown weight. From this research, it was concluded that the POC treatment of coconut bunches in peat media had a real effect on all observation parameters, namely plant height, stem base diameter, number of leaves, wet root weight, plant crown weight with the best dose found in the coconut bunch POC treatment of 80 ml/l of water